2015
DOI: 10.3390/agriculture5010030
|View full text |Cite
|
Sign up to set email alerts
|

Pine Woodchip Biochar Impact on Soil Nutrient Concentrations and Corn Yield in a Silt Loam in the Mid-Southern U.S.

Abstract: Biochar has altered plant yields and soil nutrient availability in tropical soils, but less research exists involving biochar additions to temperate cropping systems. Of the existing research, results vary based on soil texture, crop grown, and biochar properties. The objective of this study was to determine the effects of pine (Pinus spp.) woodchip biochar at 0, 5, and 10 Mg·ha

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
(53 reference statements)
7
18
1
1
Order By: Relevance
“…Due to this high C addition, several previous temperate biochar field studies advise supplemental N additions to minimize biochar induced N limitations (Brantley et al, 2015;Jones et al, 2012;Lehmann et al, 2003;Tammeorg et al, 2014;Zheng et al, 2012). However, at the 30 Mg ha -1 addition rate, we observed no decrease in soil N pools, or increase in microbial N immobilization with the biochar plots.…”
Section: Soil Moisture and Nutrientscontrasting
confidence: 59%
See 2 more Smart Citations
“…Due to this high C addition, several previous temperate biochar field studies advise supplemental N additions to minimize biochar induced N limitations (Brantley et al, 2015;Jones et al, 2012;Lehmann et al, 2003;Tammeorg et al, 2014;Zheng et al, 2012). However, at the 30 Mg ha -1 addition rate, we observed no decrease in soil N pools, or increase in microbial N immobilization with the biochar plots.…”
Section: Soil Moisture and Nutrientscontrasting
confidence: 59%
“…Aside from physical habitat, biochar's large surface area and reactivity attracts ions and low-molecular weight organic compounds; thus biochar can initially increase nutrient retention and potential sites for microbe-substrate interactions (Gul et al, 2015). Even with these known structural changes, the effect of pine-wood biochar on microbial biomass remains variable, ranging from no impact to 100% increases (Brantley et al, 2015;Domene et al, 2014;Gomez et al, 2014;Jin, 2010). Despite the wide variation in response of microbial biomass to biochar, few researchers have quantified how microbial function is altered by these induced soil physical changes in soil moisture and surface area, and chemical changes to nutrient retention and pH (Elzobair et al, 2016;Lehmann et al, 2011;Oleszczuk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eucalyptus biochar was not different from filtercake biochar, but it contributed to the lowest soil total N. Brantley et al . () suggested that combining biochar with N fertilizer could improve maize production based on increased NUE and yield compared to no biochar. Increased soil N retention through biochar could be due to increased N immobilization, reduced N losses from gases and surface erosion, and higher organic N retention on biochar surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Increased soil N retention through biochar could be due to increased N immobilization, reduced N losses from gases and surface erosion, and higher organic N retention on biochar surfaces. In addition, biochar may increase N availability by providing substrate and habitat for microorganisms (Brantley et al, 2015).…”
Section: Biochar Effects On Plant Physiological Propertiesmentioning
confidence: 99%